Shattering dawn - Krentz, Jayne Ann (Krentz, Jayne Ann. Lost night files, 2025)
"Amelia Rivers, a member of the Lost Night Files podcast team, hires private investigator Gideon Wells to catch the stalker who has been watching her. Amelia suspects the stalker may be connected to the shadowy organization responsible for the night that she and her two friends lost to amnesia-a night that upended their lives and left them with paranormal talents. Gideon suspects that Amelia is either paranoid or an outright con artist, but he takes the case despite his skepticism. He is forced to reckon with the truth when he disrupts what was intended to be Amelia's kidnapping. Now the pair are on the run, desperate to stop a killer and the people who are conducting illegal experiments with a mysterious drug that is designed to enhance psychic abilities." --